2018
DOI: 10.15252/embr.201745595
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of USP 30 in controlling basal pexophagy and mitophagy

Abstract: USP30 is an integral protein of the outer mitochondrial membrane that counteracts PINK1 and Parkin‐dependent mitophagy following acute mitochondrial depolarisation. Here, we use two distinct mitophagy reporter systems to reveal tonic suppression by USP30, of a PINK1‐dependent component of basal mitophagy in cells lacking detectable Parkin. We propose that USP30 acts upstream of PINK1 through modulation of PINK1‐substrate availability and thereby determines the potential for mitophagy initiation. We further sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
177
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(196 citation statements)
references
References 48 publications
17
177
2
Order By: Relevance
“…We see enhanced pUb accumulation in the absence of USP30 activity, despite the published observations that pUb modified chains provide a poor substrate for USP30 (9,41). How then might USP30 suppress mitophagy, as previously reported in several studies (20,(22)(23)(24)? We have previously shown that USP30 depletion enhances PINK1-dependent basal mitophagy even in the absence of Parkin (20).…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…We see enhanced pUb accumulation in the absence of USP30 activity, despite the published observations that pUb modified chains provide a poor substrate for USP30 (9,41). How then might USP30 suppress mitophagy, as previously reported in several studies (20,(22)(23)(24)? We have previously shown that USP30 depletion enhances PINK1-dependent basal mitophagy even in the absence of Parkin (20).…”
Section: Discussioncontrasting
confidence: 45%
“…USP30 is one of only two DUBs that possess a transmembrane domain. Its localisation is restricted to the outer mitochondrial membrane and to peroxisomes (18)(19)(20)(21). USP30 can limit the Parkin-dependent ubiquitylation of selected substrates and depolarisation-induced mitophagy in cell systems that have been engineered to over-express Parkin (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Cichocki et al [63] also show that the loss of Pex19 impinges upon mitochondrial targeting. Consequently, the ability to control the extent of the mitochondrial and peroxisomal localisation of Miro may be an important regulatory axis; an axis that likely includes members of an ever-growing list of proteins targeted to both organelles including USP30, Fis1, Mff, MUL1/MAPL, OMP25, BCL-XL, BCL-2, MAVS and GDAP1 [8,10,[21][22][23][24][25]. With this in mind, we propose the following model: the Miro transmembrane domain is required for Pex19 binding and peroxisomal localisation of Miro.…”
Section: Discussionmentioning
confidence: 99%
“…These include Fis1, Mff, Drp1, GDAP1, USP30, MUL1/MAPL, OMP25, MAVS, BCL-XL, BCL-2 and more recently Miro1/2 [6,10,[21][22][23][24][25][26]. These include Fis1, Mff, Drp1, GDAP1, USP30, MUL1/MAPL, OMP25, MAVS, BCL-XL, BCL-2 and more recently Miro1/2 [6,10,[21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%